2019
DOI: 10.1007/s11420-019-09705-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessments of Hand Function in First Carpometacarpal Osteoarthritis Do Not Appear to Correlate with Radiographic Findings

Abstract: Background: Thumb carpometacarpal (first CMC) osteoarthritis (OA), a degenerative process affecting hand use, is typically assessed by clinical examination and radiographs. This assessment determines treatment, but it may not reflect functional limitations. Questions/Purposes: We aimed to explore the relationship between measures of hand function and radiographs in individuals with and without first CMC OA. Methods: We designed a cross-sectional, observational pilot study, enrolling five patients with first CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
1
4
0
1
Order By: Relevance
“…More explicitly, subjects in this study with stiffer APB and FPB muscles showed better functional hand use, strength, and dexterity. When specifically comparing groups, our aforementioned prior investigation found significant differences in hand function between first CMC OA patients and control subjects, with control subjects performing better [18]. SWE metrics of muscle stiffness in the current study also revealed differences between groups, where the less stiff muscle was seen in first CMC patients.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…More explicitly, subjects in this study with stiffer APB and FPB muscles showed better functional hand use, strength, and dexterity. When specifically comparing groups, our aforementioned prior investigation found significant differences in hand function between first CMC OA patients and control subjects, with control subjects performing better [18]. SWE metrics of muscle stiffness in the current study also revealed differences between groups, where the less stiff muscle was seen in first CMC patients.…”
Section: Discussionsupporting
confidence: 64%
“…The limitations of radiographic scoring systems of first CMC OA such as the E-L system have been well reviewed [9, 12] and include poor correlation with clinical symptoms and intraoperative findings, and limited ability to guide surgical treatment. In a recent publication [18], our group demonstrated a poor correlation between basilar joint x-ray findings and measures of hand function. It follows that SWE measures of thenar eminence muscle stiffness in this study are poorly correlated with x-ray grades of first CMC OA.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Fourth, we did not track the severity of the disease as an independent variable, largely because we mixed diagnoses. We felt comfortable doing so because studies of patients with carpal tunnel syndrome 23 , trapeziometacarpal osteoarthritis 24,25 , and shoulder 26 and spine problems 27 have shown that objective measures of disease severity accounted for relatively little variation in the intensity of symptoms and magnitude of limitations. Fifth, the findings may not be applicable to different populations, different geographical areas, or different races or ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…Fontos azonban megjegyezni, hogy a radiológiai eltérések nem minden esetben, sőt inkább gyakran, csak csekély mértékben korrelálnak a kézfunkció csökkenésével, illetve a megélt fájdalommal, így mindenképpen komplex módon javasolt figyelembe venni a tüneteket, a fájdalmat, a funkcióra vonatkozó információkat, illetve a releváns kérdőívek eredményét is a kezelési terv kialakításakor (27).…”
Section: Bevezetésunclassified